RONC-23. NOVEL APPROACH TO REDUCE ACUTE ESOPHAGEAL TOXICITY IN CRANIO-SPINAL IRRADIATION USING INTENSITY MODULATED PROTON THERAPY. (4th December 2020) - Nakra, Vineet; Chilukuri, Srinivas; Gaikwad, Utpal; MP, Noufal; Patro, Kartikeshwar; T, Rajesh; Shamurailatpam, Dayananda; Sunder, Sham; Burela, Nagarjuna; T, Rishan; Tonse, Raees; K, Muthiah; et al.
Abstract: INTRODUCTION: We present our experience of a novel approach using intensity modulated proton therapy(IMPT) for cranio-spinal irradiation(CSI) leading to reduced acute esophageal toxicity and reduced treatment interruptions. MATERIAL AND METHODS: Seven children younger than 12 years old treated consecutively with CSI using IMPT were included in this study. Three among 7 children received concurrent chemotherapy(CCT). Entire vertebral body(VB) was part of target volume in all patients. The IMPT plan was generated using 3 fields with single field optimisation technique. Last 5 patients were treated using dose gradient(DG) (98-93%) deliberately created in anterior most 3-5mm of VB. Initial 2 patients were treated with intention of covering entire VB with 98% isodose. Monte Carlo algorithm was used for dose calculations and optimisation, and robustness assessed for 3mm setup and 3.5% range uncertainty. RESULTS: The CSI dose ranged from 21.6GyE to 35GyE. In patients without DG, maximum and mean dose to esophagus(36.67GyE vs. 25.45GyE, 31.53GyE vs. 20.41GyE), midline mucosa(28.95GyE vs. 25.31GyE, 21.8GyE vs. 14.61GyE) and bowel bag(32.9GyE vs. 24.27GyE, 3.59GyE vs. 3.21GyE) were higher compared to patients with DG. Both patients where DG was not created, developed grade 2 esophageal toxicities requiring supportive care and treatment interruptions(4 and 2days). All 5 patients with DG did not develop significant esophageal toxicity and had no interruptions. CONCLUSION: Creating a dose gradient over anterior VB using IMPT reduces dose to esophagus and midline mucosa leading to lower acute esophageal toxicity which potentially avoids treatment interruptions during CSI.